PENERAPAN FUNGSI PENGAWASAN INSPEKTORAL PENGAWASAN DAERAH DALAM MENUNJANG KINERJA ANGGOTA KEPOLISIAN DI WILAYAH PAPUA BARAT DAYA - Rinal Rinal; Weron Murary; Raymond R Morintoh (Ensiklopedia Research and Community Service Review, 2026)
Abstract: The purpose of this st  udy is about the Regional Inspectorate for Supervision, one of the strategic work units under the West South Papua Regional Police, which is tasked with conducting supervision and internal control within the police environment. As part of the police internal supervision system, Itwasda plays an important role in maintaining performance quality, discipline, accountability, as well as compliance with laws and operational standards within the regional police. With Itwasda in place, it is hoped that the handling process of criminal acts in the West South Papua Regional Police can run more transparently and professionally, thereby increasing public trust in the police. The Regional Supervision Inspectorate (Itwasda) of the West South Papua Police acts as an internal oversight body that conducts audits, reviews, evaluations, monitoring, and handles public complaints. This oversight function isn’t just about punishing violations; it’s also preventive and educational, aimed at guiding police officers to be more disciplined, professional, and have integrity. Normative-empirical research is used to analyze or find out how far regulations or laws are running effectively. This research was carried out at the Southwest Papua Regional Police. Data obtained directly from interviews with the community is called primary data, while data coming from library materials is called secondary data. Literature studies are conducted to get the latest information that’s related to the research problem, and in interviews, the researcher will have a dialogue or talk directly with informants about the research topic. The research findings show that the regional supervisory inspectorate is capable of carrying out its duties and functions in overseeing the actions of police officers. As the coordinator for handling all public complaints, the regional supervisory inspectorate has performed its role well, even though there is a main issue, which is the quite unpredictable and long time required to resolve public complaints. The handling of public complaints by the regional supervisory inspectorate has been done properly; however, there is a need to expand the authority of the regional supervisory inspectorate in carrying out its supervisory function regarding members suspected or alleged to have violated KEPP and/or the law. The obstacles found in the research are: mechanisms that are not streamlined, bureaucratic errors from the relevant units, the number of subbag dumasan members is insufficient compared to the overall tasks they have, discomfort in handling and taking action against colleagues, the public who do not understand the dumas mechanism, and the complicated process from investigation to making a decision.Keywords: Itwasda, Police Members, Southwest Papua.